Religion, politics and law : philosophical reflections on the sources of normative order in society - Labuschagne, Barend Christoffel, 1962-; Sonnenschmidt, Reinhard (Brill, 2009)
Exploring the pre-political en pre-legal spiritual infrastructure from which modern, liberal democracies in the West live, but cannot guarantee, this book inquires the relations between religion, politics and law from a philosophical perspective, discussing historical, systematical and practical issues.